Contemporary logistics - Johnson, James C. 1944- (Prentice Hall, 1999)
Exploring contemporary logistics, this book describes the supply channel system - from inbound movement of freight through materials management to physical distribution to customers. This book highlights topics that affect logistics channels management - including customer service, packaging, inventory management, and traffic management.